MENINGKATKAN KOMPETENSI KEPALA SEKOLAH MELAKSANAKAN SUPERVISI AKADEMIK MELALUI KEGIATAN COACHING (PEMBIMBINGAN) DENGAN POLA IN-ON-IN-ON PADA DABIN 1 KECAMATAN PARAKAN KABUPATEN TEMANGGUNG TAHUN PELAJARAN 2014/201 - Sugito Sugito (JP3 (Jurnal Pendidikan dan Profesi Pendidik), 2015)
This school action research is the result of observations of researchers in developing and monitoring the performance of teachers in the target area, that aims to enhance creativity kindergarten teachers in making props from recycled materials through group counseling.The procedure is performed in this study a shared action in two cycles, each cycle consisting of four main activities: planning, action, reflection, and evaluation.Generally based on research, indicate an increase in the percentage of 9% on the initial conditions to 45% in cycle I and 82% in cycle II, so that it can be concluded that the guidance of the group can enhance creativity kindergarten Dabin III UPT Education Departement Parakan District in Semester II Academic Year 2014/2015 in making props from recycled materials.